A Semiquantitative Non-invasive Measurement of PcomA Patency in C57BL/6 Mice Explains Variance in Ischemic Brain Damage in Filament MCAo - Knauss, Samuel; Albrecht, Carolin; Dirnagl, Ulrich; Mueller, Susanne; Harms, Christoph; Hoffmann, Christian Johannes; Koch, Stefan Paul; Endres, Matthias; Boehm-Sturm, Philipp (Frontiers in Neuroscience, 2020)
Numerous studies on experimental ischemic stroke use the filament middle cerebral artery occlusion (fMCAo) model in C57BL/6NJ mice, but lesion sizes in this strain are highly variable. A known contributor is variation in the posterior communicating artery (PcomA) patency. We therefore aimed to provide a semiquantitative noninvasive in vivo method to routinely assess PcomA patency. We included 43 male C57BL/6NJ mice from four independent studies using a transient 45 min fMCAo model. Edema-corrected lesion sizes were measured by magnetic resonance (MR) imaging 24 h after reperfusion. Time-of-flight MR angiography was performed 7 days before and 24 h after fMCAo. Scores of PcomA size measured 24 h after, but not scores measured 7 days before fMCAo were negatively correlated with lesion size. Variability in PcomA patency explained 30% of the variance in our cohort (p < 0.0001, coefficient of determination r2 = 0.3). In a simulation using parameters typical for experimental stroke research, the power to detect a true effect of d = 1 between two groups increased by 15% when an according covariate was included in the statistical model. We have demonstrated that in vivo measurement of PcomA size is feasible and can lead to increased accuracy in assessing the effect of treatments.